The teaching and learning of clothing modeling: a systematic literature review: (Revista de Ensino em Artes, Moda e Design, 2023)
The goal of this study relays on synthesizing and systematizing national and international scientific research as a way to present guidelines and didactic strategies for clothing patternmaking learning processes. Through a qualitative approach, a Systematic Literature Review (SLR) was carried out in theses, dissertations and scientific articles databases. The timeline is framed between 2010 and 2022. A whole of 625 documents were initially identified; after analyzing the metadata, 173 documents were classified into five categories: teaching and didactics, methods, ergonomics, technology and mathematics. From the inductive analysis of 36 documents classified in teaching and didactics category, the information was synthesized and systematized into five subcategories: pedagogical methodologies and innovative tools; interdisciplinarity; body dimensions and anthropometry; technology and educational resources; the integration of clothing modeling into the creative process.
Keywords: patternmaking; methods in fashion design; systematic literature review; teaching and learning process